Sengketa Tanah, Kepastian Hukum, dan Dakwah Sosial: Merekonstruksi Keadilan Agraria melalui Yurisprudensi Sosiologi Islam - Ahmad Muhamad Mustain Nasoha; Novia Eka Fitriyanti; Dyah Ayu Mawardah; Siti Fatimah Noviana Eka Ningrum; Itfifah Nurnailah Ramadhani; Hafitza Azzahra; Agatha Cahyani Setsetiahadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the relationship between land disputes, legal certainty, and the role of social da'wah from the perspective of Islamic law in Indonesia. The increasing number of agrarian conflicts indicates that land-related problems are not only caused by weaknesses in land administration systems and law enforcement but are also influenced by social and economic inequalities as well as the low level of public legal awareness. In this context, purely normative legal approaches are often insufficient to provide comprehensive and sustainable conflict resolution. This research employs a qualitative method through a library research approach, using descriptive-analytical techniques to examine various sources of Islamic law, national legal regulations, and relevant socio-religious literature. The findings reveal that the concept of maslahah (public benefit) in Islamic law can serve as an ethical and normative foundation for promoting agrarian justice that prioritizes social welfare. Furthermore, social da'wah plays a significant role in enhancing legal awareness, strengthening public understanding of land rights and obligations, and serving as a medium for mediation in resolving land conflicts at the community level. This study proposes an integrative model that combines state law, Islamic law, and customary law as an alternative framework for resolving agrarian disputes in a more just, humane, and sustainable manner in Indonesia.